The integration of spatial and non-spatial data model - Daman, Daut (2000)
This paper will discuss about the integration of spatial and non-spatial data in a single data model for a Geographical Information System(GIS) database. In recent research findings for GIS data model, geographical data depends on time constraint. We propose the integration that include the time constraint using a double cube data model based on a feature-based model. A unique key is used to access the integrated database.